78‐2: Using Physical Books as Interfaces to Digital Displays. Issue 1 (25th September 2020) - Bairaktaris, Georgios; Borgne, Brice Le; Nordman, Sirpa; Yrjänä, Samuli; Turkani, Vikram; Gosh, Rudresh; Akhavan, Vahid; Bagge, Peter; Turpela, Timo; Frohlich, David M.; Sporea, Radu A.
Abstract : A new form of interaction with digital displays is described, using the pages and binding of a physical book as the interface. This leads to a form of augmented book, or a‐book, which can seamlessly trigger multimedia content on a nearby device using embedded light, pressure or touch sensors.